Infrared and electromagnetic inspection of steel structures under load. Issue 2 (2nd July 2016) - Szymanik, Barbara; Psuj, Grzegorz
Abstract: This paper presents in detail the experimental methodologies and the results of the infrared investigation of steel samples under load. Moreover, the second electromagnetic method (EM) for nondestructive evaluation was used to monitor the fatigue process. The infrared thermography allows one to observe the global condition of the material, while the EM carries out local, detailed examination of the fatigue stage in the critical region. The presented inspection results are compared and discussed.